Development of Nuclear Target Production and Characterization Capabilities at San José State University - Esker Nicholas E.; Ard A.; Barrios B.; Botha W.; Chacon L.; Drapal J.; Guerrero M. S.; Huizar J.; Le L.; Randhawa S.; Vu P. (EPJ Web of Conferences)
We report the capabilities of a new nuclear targetry lab that has been established at San José State University (SJSU). Focusing on thin film targets for low energy nuclear reaction studies, the SJSU targetry group is able to make and characterize nuclear targets for a variety of experimental efforts and particle accelerator facilities. Current production techniques include physical vapor deposition via a resistive heating vacuum evaporator, molecular plating, cold rolling of ductile materials, solvent casting for deuterated plastic targets, among others. SJSU’s target characterization capabilities include microscopy for surface morphology, FTIR & XRD for elemental and chemical analysis, and α-energy loss for film thickness. As a primarily undergraduate and minority-serving institution, our targetry group leverages engaging targetry research as an introduction to nuclear science and a means to broaden the nuclear science pipeline.